2020
DOI: 10.1021/acs.jpcc.0c07886
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Raman Scattering Studies of Temperature- and Pressure-Driven Phase Transitions in CH3NH2NH2PbCl3 Perovskite

Abstract: Three-dimensional methylhydrazinium (CH3NH2NH2 +, MHy+) lead halides, related to the famous methylammonium (CH3NH3 +, MA+) and formamidinium (CH­(NH2)2 +, FA) perovskites, are attractive optoelectronic materials crystallizing in polar structures. In this work, temperature-dependent 1H and 207Pb magic-angle spinning (MAS) NMR, Raman as well as high-pressure Raman studies of CH3NH2NH2PbCl3 (MHyPbCl3) are reported. Raman spectroscopy reveals many similarities between phonon properties of MHy lead halides and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 59 publications
(199 reference statements)
9
39
1
Order By: Relevance
“…The remaining stretching vibrations, νasCNC, νsCNC and νNN, are located in the 990-1002, 820-832 and 1089-1098 cm −1 range, respectively. The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44].…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
See 1 more Smart Citation
“…The remaining stretching vibrations, νasCNC, νsCNC and νNN, are located in the 990-1002, 820-832 and 1089-1098 cm −1 range, respectively. The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44].…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
“…The position of the νsCNC bands is in good agreement with previous studies, i.e., this band was observed at 874 cm −1 for [MHy]Mn(HCOO)3 [20], 877 cm −1 for [MHy]Mn(H2POO)3 [42], 868 and 871 cm −1 for [MHy]PbBr3 [43] and 881 cm −1 for [MHy]PbCl3 [44]. The antisymmetric counterpart was previously observed at 1010 cm −1 for [MHy]Mn(H2POO)3 [42], 1004 cm −1 for [MHy]PbBr3 [43] and 1011 cm −1 for [MHy]PbCl3 [44]. For the [MHy]Mn(HCOO)3 crystal, this vibration was assigned to bands observed near 1092 cm −1 [20], but our DFT and previous ab initio calculations [41] showed that bands observed in the 1089-1098 cm −1 range for [DMHy]Mn(HCOO)3 originate from νNN.…”
Section: Room-temperature Ir and Raman Spectra And Assignment Of Bandssupporting
confidence: 91%
“…In lead MHPs, the substantial chemical shi range of 207 Pb signals of up to 3000 ppm and peak widths (full-width-at-half-maximum, FWHM in the range of a fraction of kHz to several tens of kHz) provides a powerful way to characterize structural properties such as Pb-X distances, Pb-X-Pb bond angles and octahedral tilts in the PbX 6 octahedra. 304,314,[353][354][355]358,359 1D NMR oen suffices for identifying and distinguishing the local coordination spheres and the impact of A and X site doping on the 207 Pb and 119 Sn shis in ABX 6 MHPs. In addition, 2D 207 Pb exchange spectroscopy has been used to gain insight into the solid-solution behavior of MAPbX 3 (X ¼ Cl, Br, I) obtained from mechanochemical synthesis.…”
Section: Cations Anions and Degradation Products In 3d Mhpsmentioning
confidence: 99%
“…The environmental stability and degradation processes of a wide variety of 3D MHPs have been investigated by multinuclear ( 1 H, 207 Pb, 119 Sn, 133 Cs) ssNMR spectroscopy techniques. 312,313,359,367,368 The hydrothermal stability and degradation of MAPbI 3 has been characterized through 1D 207 Pb NMR spectroscopy, and revealed that pristine MAPbI 3 and its degradation products, MAPbI 3 $H 2 O, and PbI 2 , have distinct chemical shis (Fig. 7a).…”
Section: Cations Anions and Degradation Products In 3d Mhpsmentioning
confidence: 99%
“…Furthermore, the proton T 1 is sensitive to phase transitions [ 26 , 27 ]. (ii) 13 C analysis, for detecting the incorporation of additives within the perovskite framework [ 28 ], for elucidating the phase composition at low temperatures [ 29 ] and for phase transition identification [ 30 ]. Both 1 H and 13 C spectra recorded at variable temperatures provide information useful for symmetry evaluation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%